2008
DOI: 10.1021/ic800457u
|View full text |Cite
|
Sign up to set email alerts
|

Silanol-Based Pincer Pt(II) Complexes: Synthesis, Structure, and Unusual Reactivity

Abstract: Aiming at the generation of a silanone intramolecularly bound to platinum, we prepared pincer-type PSiP silanol Pt(II) complexes. While a stable silanone complex was not isolated, unusual reactivity modes, involving its possible intermediacy, were observed. Treatment of the new PSiH 2P-type ligand ( o-IPr 2PC 6H 4) 2SiH 2 ( 7) with (Me 2S) 2Pt(Me)Cl yields the pincer-type hydrosilane complex [{( o- iPr 2PC 6H 4) 2SiH}PtCl] ( 8), which upon Ir(I)-catalyzed hydrolytic oxidation gives the structurally characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 90 publications
1
56
0
1
Order By: Relevance
“…Related reactivity involving oxidation at Si exclusively has also been reported (Figure , H – L ). Milstein and co‐workers observed that exposure of a Pt II ‐chloride precursor supported by a bis(diisopropylphosphanyl)silyl ligand featuring an Si‐H unit to air in benzene solution over the course of a month afforded a Pt II ‐metallosilanol species (Figure , H ). This reactivity was accelerated by addition of an Ir catalyst that had previously been shown to facilitate the hydrolytic oxidation of organosilanes to silanols .…”
Section: Resultsmentioning
confidence: 99%
“…Related reactivity involving oxidation at Si exclusively has also been reported (Figure , H – L ). Milstein and co‐workers observed that exposure of a Pt II ‐chloride precursor supported by a bis(diisopropylphosphanyl)silyl ligand featuring an Si‐H unit to air in benzene solution over the course of a month afforded a Pt II ‐metallosilanol species (Figure , H ). This reactivity was accelerated by addition of an Ir catalyst that had previously been shown to facilitate the hydrolytic oxidation of organosilanes to silanols .…”
Section: Resultsmentioning
confidence: 99%
“…Fexofenadine showed C=O stretching at 1700 cm -1 due to carboxylic group which shifted to 1680 cm -1 as doublet strong band in magnesium complex whereas in cadmium, calcium, chromium, manganese, iron chloride, iron sulfate, iron ammonium citrate, cobalt, nickel, copper and zinc complexes this band appeared in the region 1715-1720 cm -1 [24,25] complexes indicating the coordination of this moiety to the metal ions [26] (Figure 7).…”
Section: Infrared Studiesmentioning
confidence: 98%
“…[17] Pincer ligands based on P/C/P [18] or P/Si/P [19] donor sets afford interesting complexes, display unusual reactivity and find applications in catalysis. Furthermore, P/O/O and P/O/P ligands have been employed in self-assembly reactions.…”
Section: Introductionmentioning
confidence: 99%